Developing an Audiovisual Cultural Heritage Platform for Educational Purposes: A Case Study of Teacher-Involvement Using a Living Lab Approach. Issue 1 (March 2015) - Georges, Annabel; Logghe, Sara; Schuurman, Dimitri
For the last few decades, technological developments have fostered improvements in the process of digitizing audiovisual heritage. Besides the archiving of the audiovisual heritage content, it is also important to provide access to this specific content in order to pass on cultural heritage to future generations. However, in literature little is known about the needs and wants of end-users on audiovisual heritage archives. Within this paper we will assess the value of the Living Lab approach to map the needs of end-users and to facilitate user contributions. This will be done by a case study analysis of VIAA (the Flemish Institute of Archiving) that wants to unlock its digital archive for educational purposes. The main goal of this paper is to give an illustration of the Living Lab approach in order to map the needs of teachers towards an audiovisual heritage platform.